Uma arquitetura LPWAN de custo acessível para cidades inteligentes - Souza, Fernando Vinícios Manchini de (2019)
With the agglomeration of people, growing urbanization and resources gradually misused, the Smart Cities, strongly supported in the Internet of Things, appear as a counterpoint to the opti mization of resources and social welfare. However, the cost of communication using cellular net works is one of the major limiters for large-scale applications or in small cities with few resources. In this context, the objective of this work is to present an accessible systems architecture for intel ligent cities using LoRaWan technology for the communication of data collection devices. Thus, this architecture is validated through prototypes used in the university environment, to evaluate the feasibility and coverage of low cost gateways and also to investigate the complexity of open platforms for device development. The research results show that the architecture and materials presented meet their goals as a low-cost solution for smart cities.